Targeting Vascular Endothelial Growth Factor Receptor 2 (VEGFR-2): Latest Insights on Synthetic Strategies - Carolina S. Marques; Pedro Brandão; Anthony J. Burke (Molecules)
Vascular endothelial growth factor receptor 2 (VEGFR-2) is a crucial mediator of angiogenesis, playing a pivotal role in both normal physiological processes and cancer progression. Tumors harness VEGFR-2 signaling to promote abnormal blood vessel growth, which is a key step in the metastasis process, making it a valuable target for anticancer drug development. While there are VEGFR-2 inhibitors approved for therapeutic use, they face challenges like drug resistance, off-target effects, and adverse side effects, limiting their effectiveness. The quest for new drug candidates with VEGFR-2 inhibitory activity often starts with the selection of key structural motifs present in molecules currently used in clinical practice, expanding the chemical space by generating novel derivatives bearing one or more of these moieties. This review provides an overview of recent advances in the development of novel VEGFR-2 inhibitors, focusing on the synthesis of new drug candidates with promising antiproliferative and VEGFR-2 inhibition activities, organizing them by relevant structural features.